Effect of transcutaneous auricular vagus nerve stimulation on stress regulation: an EEG and questionnaire study - Kim, Woo-Jin; Lee, Yun-Sung; Hong, Ki Hwan; Choi, Hyuk; Song, Jae-Jun; Hwang, Han-Jeong (Frontiers in Digital Health, 2025)
IntroductionTranscutaneous auricular vagus nerve stimulation (taVNS) has demonstrated efficacy in alleviating stress-related symptoms, yet its underlying neurophysiological mechanisms remain incompletely understood. In this study, we aimed to elucidate the effects of taVNS on stress regulation by employing self-report surveys and electroencephalography (EEG) measures.MethodsParticipants performed mental arithmetic (MA) and 2-back tasks to induce stress, receiving either taVNS or sham stimulation in a randomized, crossover design. Resting-state EEG was recorded at baseline and immediately after each stress-inducing task—thereby capturing persisting taVNS-induced changes in neural activity—and subjective stress levels were assessed immediately before and after stimulation.ResultsThe survey results showed a significant increase in perceived stress following the tasks in the sham condition, whereas stress levels in the taVNS condition did not significantly change. Power spectral density (PSD) analyses revealed that theta and alpha band power in the frontal region significantly decreased only in the sham condition, suggesting elevated stress. Furthermore, whole-brain network analysis indicated a significant reduction in theta band path length in the taVNS condition following both tasks, pointing to enhanced global network efficiency that may help prevent stress escalation.DiscussionBy demonstrating distinctive EEG and behavioral differences between taVNS and sham stimulation, this study provides a neurophysiological basis for taVNS as a non-invasive intervention for stress regulation. Future research involving a more diverse participant pool and optimization of taVNS parameters will further clarify its therapeutic potential.